Effects of beta-hydroxy beta-methyl butyrate calcium combined with exercise therapy in patients with cardiac disease: a study protocol for clinical trial. Issue 2 (8th February 2023) - Ikeda, Takashi; Miyazawa, Ryo; Inoue, Eisuke; Iso, Yoshitaka; Nakamura, Daisuke; Abe, Satoko; Hachisu, Mitsugu; Tashiro, Naonori; Iguchi, Akihiro; Aimoto, Kenji; Nakamura, Shoko; Ichikawa, Hiroo
Abstract : Introduction: The current treatment for heart disease consists of exercise therapy in addition to pharmacotherapy, nutritional support and lifestyle guidance. In general, nutritional support focuses on protein, salt and energy restrictions, with no active protein or amino acid intake in cases involving moderate or higher renal failure. From this perspective, patients with cardiac disease are at high risk of frailty. Beta-hydroxy beta-methyl butyrate (HMB) is a metabolite of leucine. HMB is widely used for muscle strengthening and can be safely ingested even by patients with renal failure. The proposed study protocol will investigate the effects of HMB-calcium (HMB-Ca) administered in combination with comprehensive cardiac rehabilitation for muscle strength, muscle mass and cardiac function in patients with cardiac disease during the convalescent period. The primary outcome will be knee extensor strength. Secondary outcomes will be gross isometric limb strength and skeletal muscle mass. Methods and analysis: This study will be a single-blinded, randomised, controlled trial with parallel comparisons between two groups. The study period will be 60 days from the start of outpatient cardiac rehabilitation. Participants will be randomly divided into two groups: an HMB group consuming HMB-Ca one time per day for 60 days; and a Placebo group consuming reduced maltose once one time per day for 60 days. Exercise therapy will be performed by both groups. Ethics and dissemination: The study protocol will be published in a peer-reviewed journal. Ethics approval was provided by the Showa University Clinical Research Review Board. Trial registration number: jRCTs031220139; Japan Registry of Clinical Trails.